The incremental value of magnetic resonance imaging for breast surgery planning - ÖZKAN GÜRDAL, SİBEL; Ozcinar, Beyza; Kayahan, Munire; Igci, Abdullah; Tunaci, Mehtap; Ozmen, Vahit; Acunas, Gulden; Yavuz, Ekrem; Kecer, Mustafa; Muslumanoglu, Mahmut (My University, 2013)
The aim of this study was to evaluate the effect of breast magnetic resonance imaging (MRI) on preoperative or intraoperative surgical planning.